The Effect of Leucine Supplementation on Sarcopenia-Related Measures in Older Adults: A Systematic Review and Meta-Analysis of 17 Randomized Controlled Trials - Guo, Yufei; Fu, Xiaoya; Hu, Qingjing; Chen, Lihua; Zuo, Hui (Frontiers in Nutrition, 2022)
Background: The role of leucine in sarcopenia prevention remains unclear. We aimed to summarize the published data from randomized controlled trials (RCTs) to estimate the effect of leucine supplementation on sarcopenia-related measures in older adults. Methods: A systematic literature search was performed using the electronic databases PubMed, Embase, and Web of Science with restriction to randomized controlled trials design from January 1, 2009 to March 19, 2022. Sarcopenia-related measures included handgrip strength, total lean mass, gait speed, leg press, 6-min walk test, short-physical performance battery, timed up-and-go test and 30-s chair-stand test. Fixed- and random-effects meta-analysis models were used to generate pooled weighted mean differences (WMDs) and 95% CIs. Heterogeneity was examined in subgroup and sensitivity analyses. Publication bias assessments were performed. Results: A total of 17 RCTs enrolling 1418 subjects were identified. Leucine-isolated supplementation showed no effect on total lean mass (WMD =0.03 kg, 95% CI: -0.51, 0.57, P =0.917), handgrip strength (WMD =1.23 kg, 95% CI: -0.58, 3.03, P =0.183) and leg press (WMD =-1.35 kg, 95% CI: -7.46, 4.77, P =0.666). However, leucine-combined supplementation including vitamin D showed a significant improvement in handgrip strength (WMD =2.17 kg, 95% CI: 0.24, 4.10, P =0.027) and gait speed (WMD =0.03 m/s, 95% CI: 0.01, 0.05, P =0.008). Conclusions: Leucine-isolated supplementation did not improve muscle mass and strength in elderly. However, leucine-combined supplementation including vitamin D exhibited a significant benefit for muscle strength and performance including handgrip strength and gait speed in older adults. A combination of nutritional supplements would be a viable option for improving sarcopenia.